Local memory: A vision of Arequipa's historiography - Espinoza de la Borda, Álvaro (2010)
A better understanding of the country requires a greater knowledge of the peoples that make it up. In this sense, local stories will contribute a lot to it. This constitutes a panoramic recount of Arequipa's historiography that has numerous representatives and varied production; which has increased significantly in recent decades with the work of new generations of historians.